Bartek is one of local melon varieties mainly cultivated in Pemalang, Central Java. Bartek has three variations of fruits; Long-Green, Ellips-Green, and Yellow. Chromosome characterization of the Bartek was investigated to determine the genetic variation. The main purpose of this research was to determine the genetic characters of Bartek including chromosome number, mitosis, cell cycle, and karyotype. Squash method was used for chromosome preparation. The results showed that all of Bartek observ - BUDI SETIADI DARYONO; DIAN ARUNI KUMALAWATI (Bogor Agricultural University, Indonesia, 2011)
Bartek is one of local melon varieties mainly cultivated in Pemalang, Central Java. Bartek has three variations of fruits; Long-Green, Ellips-Green, and Yellow. Chromosome characterization of the Bartek was investigated to determine the genetic variation. The main purpose of this research was to determine the genetic characters of Bartek including chromosome number, mitosis, cell cycle, and karyotype. Squash method was used for chromosome preparation. The results showed that all of Bartek observed in this study have similar diploid (2n) chromosome number = 24. According to the total number of chromosome, Bartek is closer to melon than cucumber. The mitotic analysis exhibited that the Bartek has similar karyotype formula, 2n = 2x = 24m. Based on the R value of the three kinds of Bartek (R < 0.27), it indicated that three kinds of Bartek were considered to be originated from similar species and one of melon varieties (Cucumis melo L. var. Bartek).